Climate change and hydropower in the Southern African Power Pool and Zambezi River Basin: System-wide impacts and policy implications. (April 2017) - Spalding-Fecher, Randall; Joyce, Brian; Winkler, Harald
Abstract: This paper examines climate change impact on hydropower will affect the expansion of the regional electricity system, as well as system costs and greenhouse gas emissions. The output from major Zambezi hydropower plants could decline by 10–20% under a drying climate, while wetting of the basin produces only a marginal increase. At a regional level, the increases in electricity generation costs are relatively small (less than 1% over the long term), but could reach 20–30% in the near term for hydro-dependent countries (e.g. Mozambique and Zambia). Because some hydropower could be displaced by coal, regional greenhouse gas emissions could increase by the equivalent of a large coal-fired power station. The risks to regional electricity systems highlight the need for strong cooperative governance arrangements to manage shared water resources in the region, which could be bolstered by recent political initiatives. Beyond the level of individual investments, a policy shift is needed to integrate climate change and upstream development considerations into national and regional electricity planning, supported by relevant tools. In addition, the potential for increased carbon emissions has implications for the commitments of southern African countries under the Paris Agreement to the UNFCCC. Highlights: Zambezi hydropower output could decline by 10–20% under a drying climate. Near term system generation costs could rise 20–30% for hydro-dependent countries. GHG emissions could also increase under a dryer climate. This could jeopardize countries' climate mitigation commitments. Regional infrastructure investments must consider potential climate impacts.